Ripple Effect How Empowered Involvement Drives Word of Mouth - Oetting, Martin (Forschungsgruppe Konsum und Verhalten, 2009)
Everyone in marketing is talking about word of mouth (WOM). At a time when traditional advertising is struggling, conversations between consumers - the most trusted source of product information - have taken on an entirely new dimension on the Internet. While considerable research on the effects and spread of WOM has been carried out over the past sixty years, surprisingly few scholars have tried to find out how to stimulate it. Martin Oetting seeks to close that gap. Based on involvement and empowerment research, this is the first scientific study connecting word of mouth with a participatory marketing approach, thus providing an answer to what may be marketing's most pressing question: how to strategically harness the power of blogs, Facebook, and the Social Web.